SHORT AND LONG-TERM RESULTS OF LAPAROSCOPIC ESOPHAGOCARDIOMYOTOMY WITH FUNDOPLICATION (HELLER-PINOTTI SURGERY) IN THE TREATMENT OF NON-ADVANCED ACHALASIA (MEGAESOPHAGUS) - João Bosco CHADU JUNIOR; Jefferson Alvim de OLIVEIRA; Adilson Gomes FAION; Bruno ZILBERSTEIN (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2024)
ABSTRACT BACKGROUND: Videolaparoscopic esophagocardiomyotomy with fundoplication has been a widely used technique for the treatment of achalasia. This study analyzes the safety and effectiveness of the technique in the treatment of non-advanced achalasia (megaesophagus) in a Brazilian federal university public hospital. AIMS: To evaluate the short- and long-term results of videolaparoscopic treatment of non-advanced megaesophagus in a public university hospital in Brazil, employing the esophagocardiomyotomy technique with fundoplication. METHODS: The medical records of 44 patients who underwent surgical treatment for non-advanced achalasia at the Clinical Hospital of Federal University of Uberlândia (UFU-MG), Minas Gerais, from January 2001 to July 2021 were analyzed. The following data were evaluated: gender, age, etiology, radiological classification of Rezende-Alves and Ferreira-Santos, immediate and late complications (mean follow-up of 31.4 months), need or not for conversion to open access, postoperative reflux, performance or not of endoscopic esophageal dilation in the preoperative period, postoperative mortality, frequency of pre and postoperative symptoms (persistent dysphagia, regurgitation, heartburn, vomiting, odynophagia, and weight loss), surgery time, hospital stay, duration of dysphagia, pre and postoperative weight, and Eckardt score. RESULTS: Among the analyzed patients, 23 (52.3%) were male, and 21 (47.7%) were female, with a mean age of 50.8 years. No early complications were recorded and there were 27.2% cases of late gastroesophageal reflux. Postoperative weight gain was 81.8% and the success rate of surgery according to the Eckardt score was 84.1%. CONCLUSIONS: Esophagocardiomyotomy with fundoplication is an effective and safe technique for the treatment of non-advanced achalasia.